Holiness in Victorian and Edwardian England: Some ecclesial patterns and theological requisitions - Goroncy, Jason A. (HTS teologiese studies, 2017)
This essay begins by offering some observations about how holiness was comprehended andexpressed in Victorian and Edwardian England. In addition to the ‘sensibility’ and ‘sentiment’that characterised society, notions of holiness were shaped by, and developed in reaction to, dominant philosophical movements; notably, the Enlightenment and Romanticism. It thenconsiders how these notions found varying religious expression in four Protestant traditions – he Oxford Movement, Calvinism, Wesleyanism, and the Early Keswick movement. Injuxtaposition to what was most often considered to be a negative expression of holinessassociated primarily with anthropocentric and anthroposocial behaviour as evidenced in thesetraditions, the essay concludes by examining one – namely, P.T. Forsyth – whose voice calledfrom within the ecclesial community for a radical requisition of holiness language as afundamentally positive reality describing the divine life and divine activity. The relevance of astudy of the Church’s understanding of holiness and how it sought to develop its doctrinewhile engaging with larger social and philosophical shifts endure with us still.